Profile of patients with hematological toxicity grades 3 and 4 and gastrointestinal toxicity of patients undergoing chemotherapy - Matos, Renata Almeida de; Mendonça, Érica Toledo de; Salgado, Patrícia de Oliveira; Souza, Cristiane Chaves de (Ciência e Natura, 2022)
The administration of chemotherapeutic agents may lead to the occurrence of toxicities in organic systems not affected by cancer. This study aimed to evaluate the profile of patients with hematological toxicity grades 3 and 4 and gastrointestinal toxicity of patients undergoing chemotherapy. There was a prevalence of 48.70% of gastrointestinal toxicity, 42.20% of hematological toxicity and 9.10% of hematological and gastrointestinal toxicities. The most common symptoms of toxicity grade 3 was Hb <8.0 - 6,5g/dl (47.05%), and of hematological toxicity grade 4 was febrile neutropenia (44.44%). Patients with gastrointestinal toxicity presented vomiting (43.69%), diarrhea (21.84%) and nausea (20.16%). There was an association between the development of toxicities and the variables purpose of chemotherapy, modality of treatment, type of cancer staging and smoking. Knowing the profile of these patients may help the nurse in the early identification of symptoms for adoption of clinical protocols aimed at minimizing the symptoms and improving the patient’s coping process of the treatment.